The Function of Community Participation in the Implementation of Regional Development - Rifda Akmaliya (Socio Legal and Islamic Law, 2022)
Society is a social being who always wants to socialize within the scope of its territory. In social life, the concept of planning and implementation is important, with community involvement becoming a benchmark for achievement in a regional program development. the success or failure of the implementation program depends on the ratio of their wishes. if the obligations, duties and authorities of the community are fulfilled in participation, it will have a major impact on the success of the program. according to what they had planned. as for some forms of participation in the development program which are in the form of money, property, labor, skills, ideas, social, decision-making processes, and representation.Â  The writing of this article describes the contents of the functions, benefits, and roles of the community based on their rights, obligations, duties and authorities. in coordinating the system of planning, monitoring, implementation.Â  Keywords : Actors, Function, Benefits Of Community ParticipationÂ